Implementation of Liveworksheets-Based E-LKPD Using Discovery Learning to Enhance Students’ Creative Thinking and Collaboration Skills in Salt Hydrolysis - Auliya Rahmah Auliya; Parham Saadi; Rilia Iriani (Jurnal Inovasi Pendidikan Kimia, 2025)
Low levels of students’ creative thinking and collaboration need to be addressed to support the generation of new ideas and effective problem-solving in chemistry, particularly in challenging topics such as salt hydrolysis. This study examined differences in (1) creative thinking skills and (2) collaboration skills between students who learned using Discovery Learning–based electronic student worksheets (e-LKPD) delivered via Liveworksheets and those who used Discovery Learning–based printed student worksheets, as well as (3) students’ perceptions of the learning experience. A quasi-experimental design with a nonequivalent control group was employed. Data were collected using both test and non-test instruments. Independent t-test results comparing pretest and posttest scores revealed a significant improvement in creative thinking skills among students using Liveworksheets-based e-LKPD (Sig. 2-tailed ≈ 0.00 < 0.05). Similarly, a significant difference in collaboration skills was observed between the two groups (Sig. 2-tailed ≈ 0.00 < 0.05). Student feedback indicated positive responses toward the implementation of Liveworksheets-based e-LKPD and Discovery Learning–based worksheets. These findings suggest that the integration of Discovery Learning with Liveworksheets-based e-LKPD can effectively enhance students’ creative thinking and collaboration in learning complex chemistry topics, providing a promising approach for improving engagement and higher-order thinking skills